Evaluation of artificial reef habitats as reconstruction or enhancement tools of benthic fish communities in northern Yellow Sea. (September 2022) - Song, Minpeng; Wang, Jiahao; Nie, Zhaoyi; Wang, Lu; Wang, Jinxiao; Zhang, Jiating; Wang, Yuxin; Guo, Zhansheng; Jiang, Zhaoyang; Liang, Zhenlin
Abstract: Artificial reefs have been widely deployed in the northern Yellow Sea. However, the differences in the ecological benefits on different types of artificial reef habitats are still poorly understood. In this study, the temporal and spatial differences on benthic fish communities were evaluated among concrete artificial reef habitat (CAR), rocky artificial reef habitat (RAR), ship artificial reef habitat (SAR) around Xiaoshi Island in northern Yellow Sea. The results indicated that all three types of artificial reef habitats can enhance the diversity variables of benthic fish communities, and fish abundance, species richness and Shannon-Wiener index of CAR were generally better than the other two. CAR and RAR hosted similar community composition of benthic fish, and all types of habitats showed significant differences in community composition between winter-spring and summer-autumn. Environmental factors, especially water temperature, can also affect the community composition by affecting the migration of temperature-preferred species. Overall, the enhancement effects of artificial habitats on fisheries productivity varied with fish species and reef types. This study will help to understand the ecological effects of different types of artificial reefs in northern Yellow Sea, and then could give an insight for scientific construction of artificial reefs in this region. Graphical abstract: Unlabelled Image Highlights: All artificial reef habitats enhanced abundance, biomass, species richness and diversity index of benthic fish communities dominated by rocky reef fish Artificial reef habitat type influenced benthic fish community structure Concrete artificial reef habitat performed generally better ecological effect than other artificial reef habitats Benthic fish community composition showed strong seasonal variation in all habitats